2020
DOI: 10.1038/s41598-020-67529-x
|View full text |Cite
|
Sign up to set email alerts
|

Object detection based on an adaptive attention mechanism

Abstract: Object detection is an important component of computer vision. Most of the recent successful object detection methods are based on convolutional neural networks (CNNs). To improve the performance of these networks, researchers have designed many different architectures. They found that the CNN performance benefits from carefully increasing the depth and width of their structures with respect to the spatial dimension. Some researchers have exploited the cardinality dimension. Others have found that skip and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…It was initially developed in 2014 for natural language processing applications [20], since then it has been widely used for different applications [30], in particular, computer vision tasks [21,31]. Its potential to enhance mostly CNN-based methods has been reported [32]. In addition, it has been used in conjunction with recurrent neural network models [33][34][35][36], and graph neural networks [37,38].…”
Section: Attention Mechanism In Deep Learningmentioning
confidence: 99%
“…It was initially developed in 2014 for natural language processing applications [20], since then it has been widely used for different applications [30], in particular, computer vision tasks [21,31]. Its potential to enhance mostly CNN-based methods has been reported [32]. In addition, it has been used in conjunction with recurrent neural network models [33][34][35][36], and graph neural networks [37,38].…”
Section: Attention Mechanism In Deep Learningmentioning
confidence: 99%
“…The fully connected layer is usually used as a classifier of CNN, but too many parameters of the fully connected layer will increase the calculation amount of the network and thus slow down the training speed and also easily appear the overfitting problem [38]. Global average pooling (GAP) is a global average of all pixels in the feature map of each channel and obtains the output of each feature map [39][40][41]. GAP directly removes the features of black box in the fully connected layer and gives each channel practical significance; then, the vectors composed of these output features will be sent to the classifier for classification directly [42].…”
Section: Global Averagementioning
confidence: 99%
“…Recent research has shown that the attention mechanism has been commonly used to preserve the dependency of features in certain computer vision tasks such as object detection [54], image classification [52] [53], and image segmentation [48]- [51]. The attention method enables the model to attend more closely to essential features without any external supervision, and it can avoid identical feature maps at various scales to lead to better feature representation.…”
Section: Introductionmentioning
confidence: 99%